COMMUNICATIVE TRANSLATION METHOD OF ENGLISH INDONESIAN TRANSLATION IN BOOK “THE ONE MINUTE MANAGER” BY KENNETH BLANCHARD, PH.D AND SPENCER JOHNSON, M.D - Suhendar Suhendar (STIBA IEC JAKARTA, 2019)
The objective of this research mainly aims to find out the proofs that the translator used communicative translation in Indonesian book version. This paper was directed to answer two basic questions about the strategies that used by the translator to translate in target language and the proofs which shows that in target language the translator used communicative translation method. The writer used the theory of Newmark about communicative translation method that is used to analyze the data. It amplifies that analysis based on the theory by expert will make easier to analysis. This research used qualitative method in which the writer undertakes research through describing the data. The writer found that the translation method that used by the translator is communicative translation method. In translation by the translator pay attention the meaning of source language so that the message in target language can be received by the readers.